Economics of grids, clouds, systems, and services : 15th International Conference, GECON 2018, Pisa, Italy, September 18-20, 2018, Proceedings /: 15th International Conference, GECON 2018, Pisa, Italy, September 18-20, 2018, Proceedings. (2019) - Unknown
No abstract available